PENGUJIAN PRODUKSI SEL DEBARYOMYCES SP. PADA BEBERAPA MEDIA UNTUK PENGENDALIAN HAYATI PENYAKIT ANTRAKNOSA PADA CABAI - Dian Indratmi (Jurnal Gamma, 2010)
Result of research Dian Indratmi previously (2000, 2001, and 2002) indicated among antagonisfungi that shown potential inhibition Colletotrichum gloeosporioides better were fructoplant yeastinoculan especially Debaryomyces sp. For evaluation of efficacy yeast Debaryomyces sp.as apotential biokontrol agent of chilli anthracnose or to develop this agent as biopesticide, it is importantto have available culture media that maximize production at low cost.The aimed of this research to find out a low cost media culture formulation for yeast fructoplantbiomass production for their application on field to suppressed anthracnose disease on pepper.The laboratory experiment with Complete Randomized Design and 6 replication. There were11 treatment, it’s A = malt extract liquid media; B = malt extract liquid media + pepper extract; C= corn meal liquid media; D = corn meal liquid media + pepper extract; E = sugar potato extractliquid media; F = Alioshina liquid media; G = sugar mixture of rice and bran liquid media; H =sugar pepper extract liquid media; I = maize solid media; J = waste water rice media; K = ipomoealiquid media.Results of the experiment indicated 11 of the yeast media culture test can as a substrate foryeast biomass production. Yeast Debaryomyces sp that cultured on the substrate corn meal liquidmedia that added with or without pepper extract resulted better weight and quantity cell of yeastDebaryomyces sp. The yeast for their growing needed a rather acid substrate, it’s about pH 4.79-6.07.